Utilization Of Sterol Glycosides In Fame (Fatty Acid Methyl Ester) Byproducts From The Biodiesel Industry - Noor Ridha Yanti; Meilana Dharma Putra; Agung Nugroho; Hesty Heryani (Universitas Lambung Mangkurat, 2019)
In recent years, the development of renewable energy such as biodiesel has been widely researched throughout the world as technology advances in the era of Industry 4.0. At the final station of biodiesel production in the maturation tank, the by-products will form by-products in the form of sterol glycosides in Fatty Acid Methyl Esters which have not been utilized. This study aims to determine the volume of biodiesel from a mixture of sterol glycosides with a ratio of 0.5% H2SO4 catalyst concentration; 1%; 1.5% and 2% and tested their characteristics in accordance with the Indonesian National Standard (SNI 7182: 2015). Biodiesel production was carried out by esterification with a molar ratio of 1:6 (sterol glycoside: methanol) to variations in H2SO4 catalyst concentration. The results of the highest yield volume biodiesel were obtained from a catalyst concentration of 1.5% of 28.02% and the lowest yield of 17.50% in a 0.5% catalyst. Based on the characteristic test of biodiesel by varying the concentration of catalyst H2SO4 obtained density of 852 – 862 kg m-3, viscosity of 4.642 – 4.950 mm2 s-1 and saponification number of 191.007 – 198.164 mg-KOH g-1 according to standard characteristics SNI 7182:2015, while for the water content of 0.1965 – 0.1976% and acid numbers of 2.151 – 3.232 mg-KOH g-1 isn’t according to standard characteristics. Based on research, pre-treatment treatments was recommended before the refining process to reduce the amount of acid and moisture content so according to standard characteristics.